Pola Komunikasi Komunitas Tradwife di Eropa, Amerika Serikat, Australia dalam Era Digital Media - Wahyuning Lintas Utami (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2024)
The article discusses the "traditional wife" community, a group of women or wives who prioritize life values based on the social norms of women's roles in 1959. These norms position women in domestic spaces, dedicating themselves to the functionality of a family while placing the husband as the breadwinner. This article seeks to explore why, in an era where everything is measured by materialistic values, there has emerged a community of women who do not prioritize material achievements but instead choose to maximize their roles in more private domestic spaces. The article is written using an interpretative qualitative research method through literature studies, Instagram observations, website reviews, and interviews with academics specializing in women's and gender issues, as well as interviews with Indonesian women who have lived in Canada for more than five years. It also presents several facts related to the "traditional wife" phenomenon, which is viewed positively in some aspects. However, its negative side is considered a promotion of racial issues that favor white supremacy.